Tumor-associated macrophages: role in cancer development and therapeutic implications - Salmaninejad, Arash; Valilou, Saeed Farajzadeh; Soltani, Arash; Ahmadi, Sepideh; Abarghan, Yousef Jafari; Rosengren, Rhonda J.; Sahebkar, Amirhossein (Cellular oncology (Dordrecht), 2019)
Background Tumor-associated macrophages (TAMs) are known to play important roles in the initiation and progression of human cancers, as well as in angiogenesis. TAMs are considered as main components of the tumor microenvironment. Targeting TAMs may serve as a therapeutic strategy for the treatment of cancer. In this review, the signaling pathways, origin, function, polarization and clinical application of TAMs are discussed. The role of TAMs in tumor initiation, progression, angiogenesis, invasion and metastasis are also emphasized. In addition, a variety of clinical and pre-clinical approaches to target TAMs are discussed. Conclusions Clinical therapeutic approaches that show most promise include blocking the extravasation of TAMs along with using TAMs as diagnostic biomarkers for cancer progression. The targeting of TAMs in a variety of clinical settings appears to be a promising strategy for decreasing metastasis formation and for improving patient outcome.